Rancang Bangun Aplikasi Kuis Mobile Berbasis Android Untuk Pembelajaran Ips Di Kelas 5 Sd Dengan Metode Waterfall - Mellia Cristanty Sinuhaji (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2025)
Social Science (IPS) learning in 5th grade elementary schools often uses methods that are less interactive and less engaging for students, affecting the effectiveness of learning. This research aims to design and develop a mobile quiz application based on Android using the Waterfall method to support IPS learning for 5th grade students. The research scope includes needs analysis, design, implementation, testing, and maintenance of the quiz application. The Waterfall method is used because it provides structured and systematic stages in application development. The results show that the quiz application can increase students' interest and understanding of IPS material through an interactive and enjoyable learning method. In conclusion, the mobile-based quiz application can serve as an effective alternative learning media for 5th grade students. Suggestions include further feature development and content expansion to optimize the application's use in the learning process.